2006
DOI: 10.1080/02713680600760493
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oximetry Using Intravitreal Illumination

Abstract: Retinal oximetry using intravitreal illumination has been demonstrated. As a research tool, intravitreal illumination addresses several difficulties encountered when performing retinal oximetry with transcorneal illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…1,4,26,39 Using this relationship, the maximum error in λ min from our human vein data of ± 0.8 nm corresponds to ± 2.3% oxyhemoglobin saturation. The uncertainty of the measurements made using the ROx-3 is in the range we measured elsewhere and what we need for testing the potential use of a retinal oximeter clinically.…”
Section: Oxygen Saturation Errormentioning
confidence: 99%
See 4 more Smart Citations
“…1,4,26,39 Using this relationship, the maximum error in λ min from our human vein data of ± 0.8 nm corresponds to ± 2.3% oxyhemoglobin saturation. The uncertainty of the measurements made using the ROx-3 is in the range we measured elsewhere and what we need for testing the potential use of a retinal oximeter clinically.…”
Section: Oxygen Saturation Errormentioning
confidence: 99%
“…Our prior work showed that background, light path length, blood hemoglobin concentration, and other variations in measurements were independent of wavelength in the spectral range used for BGO when the glint was removed using invasive offaxis illumination. 1,26 Similarly, the optical light filtration used in the ROx-3 appears to overcome these challenges.…”
Section: On-axis Blue-green Oximetry and Removal Of The Retinal Vessementioning
confidence: 99%
See 3 more Smart Citations